2022
DOI: 10.1029/2022wr032067
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Index‐Based Partitioning of Evapotranspiration Is Deficient in Grazed Systems

Abstract: Around 60% of the precipitated water is returned to the atmosphere by evapotranspiration (ET) (Oki & Kanae, 2006). Unsurprisingly, ET plays a major role in influencing the water and climate cycles components at both local and global scales (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Another source of uncertainty is the absence of data related to partitioning of ET into E and T. In our analysis, for simplicity, we also implicitly assumed that either ET retrieved from the remotely sensed data is largely contributed by transpiration (Subsection 3.3), which is the water extracted from bls by the plants (see Equations and ), or the transpired water is closely correlated with total ET (see Equation ). In reality, this may not be true, depending on the contributions from soil evaporation and interception (Raghav et al., 2022). Again, an advanced partitioning of ET into E and T than the one adopted here, which could generate a more accurate estimate of the two components and their seasonal variability, is expected to further improve seasonal recharge estimates.…”
Section: Methodological Limitations and Discussionmentioning
confidence: 99%
“…Another source of uncertainty is the absence of data related to partitioning of ET into E and T. In our analysis, for simplicity, we also implicitly assumed that either ET retrieved from the remotely sensed data is largely contributed by transpiration (Subsection 3.3), which is the water extracted from bls by the plants (see Equations and ), or the transpired water is closely correlated with total ET (see Equation ). In reality, this may not be true, depending on the contributions from soil evaporation and interception (Raghav et al., 2022). Again, an advanced partitioning of ET into E and T than the one adopted here, which could generate a more accurate estimate of the two components and their seasonal variability, is expected to further improve seasonal recharge estimates.…”
Section: Methodological Limitations and Discussionmentioning
confidence: 99%
“…In [128], the authors explore similar relationships between leaf area index (LAI) and ETa and determined that LAI explains 43% of variability in global T/ET. However, more robust methodologies that consider factors such as water use efficiency and vapor pressure deficit may lead to improved estimates of E and T [108,129]. Those variables were not measured at our site at the time of this study.…”
Section: Restoration Landscapementioning
confidence: 99%
“…Notably, a few recent studies have indicated improved capabilities of plant hydraulic models to capture ET, though primarily during specific hydroclimatic periods such as periods that are dry 32 or have high vapor pressure deficit (VPD) 33 . Given that model performance and ET partition changes with hydroclimatic regimes [34][35][36] different model representations likely result in distinct ET partitions. Here we evaluate the limitation of model structures on accurately estimating ET and ET partitioning by comparing the performances of empirical and plant hydraulic models with a machine-learning (ML) based model, which is not restricted by assumptions of model structure or pre-defined relations between hydroclimatic conditions and stomatal response.…”
Section: Mainmentioning
confidence: 99%